TINDAK TUTUR KEARIFAN LOKAL YOGYAKARTA PADA FILM-FILM PENDEK DI KANAL YOUTUBE PANIRADYA KAISTIMEWAN - Fatonah, Devi Umi; Nurhayati, Endang (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
This research aims to reveal the types, characteristics and functions of speech acts that show Yogyakarta local wisdom in short films on the Paniradya Kaistimewan YouTube channel. This research uses a sociopragmatic approach with descriptive qualitative research methods. The data in this research is speech in the form of words, phrases, clauses or sentences that show the local wisdom of Ngayogyakarta in short films on the Paniradya Kaistimewan YouTube channel. How to collect data by listening, making transcriptions and writing speeches. The research tool used is the researcher himself, assisted by data cards. How to validate data using semantic validity, theoretical triangulation, and stability reliability. The results of the research show: 1) direct literal with the characteristics of using the lingual unit